MULTIPLEX DETECTION OF TUMOR MARKERS FOR DIFFERENT STAGES OF COLORECTAL CANCER - L. L. Akhmaltdinova; V. B. Sirota; V. A. Zhumalieva; I. A. Kadyrova; D. B. Babenko; Z. B. Tauesheva; D. Zh. Taizhanova; A. S. Ibraeva; O. V. Avdienko (Сибирский онкологический журнал, 2021)
Introduction. Colorectal cancer is one of the most common cancers worldwide. In the Republic of Kazakhstan, over the past decade, the incidence rates of colon and rectal cancers have increased by 23 % and 17 %, respectively. Although colorectal cancer screening rates have increased over time, it is necessary to identify new serum markers for early detection and prognosis of this cancer. The aim of the study was to evaluate the  diagnostic value of serum biomarkers for colorectal cancer. Material and Methods. Biomarkers were studied by immunofluorescence method using xMap technology, which included simultaneous immunofluorescence determination on magnetic spheres CA125, CA15–3, CA19–9, CEA, CYFRA21–1, sFAS, sFasL, HE4, Osteopontin, VEGF-A, pd-L1. Results. The study showed no significant differences in the levels of markersbetween healthy subjects (control group) and patients with bowel diseases. In cancer patients, СEA and OpN markers increased with increasing tumor stage, and were significantly higher than those observed in patients with bowel diseases and controls. The CA125 marker was significantly higher in patients with stage IV cancer then in patients with I–III stages. Conclusion. Our study revealed that the new pd-L1 marker can serve as a significant biomarker for colorectal cancer.